Community-based physical activity and wheelchair mobility programs for individuals with spinal cord injury in Canada: Current reflections and future directions. (2nd November 2017) - Best, Krista L.; Arbour-Nicitopoulos, Kelly P.; Sweet, Shane N.
Abstract : Rationale: A clear need has been identified to find strategies and opportunities, beyond services provided during rehabilitation, to enhance community-based mobility and leisure-time physical activity (LTPA) participation among members of the spinal cord injury (SCI) population. Method: This review of existing mobility and LTPA programs that are available for individuals with SCI in Canada reflects the authors' current knowledge of existing evidence-based and community-based programs. The authors aim to highlight the gaps between existing programs and future needs. Results : The major gaps identified in this brief clinical report include the need for: community-based mobility training programs, patient reported outcomes, assessment of long-term impact of programs, identifying the best approaches for program delivery, and developing researcher-stakeholder partnerships. Conclusion : Evidence-based mobility programs and community-based LTPA do exist, and the available research shows their promise. Despite the growing research for LTPA and mobility programs among adults with SCI, many gaps remain. Additional partnerships, community engagement practices, service program funding and health policy changes are needed to address the highlighted gaps to optimize community-based programs and enhance the lives of adults with SCI.